THE EFFECT OF TAXATION KNOWLEDGE AND TAX SANCTIONS ON TAXPAYER COMPLIANCE WITH AWARENESS OF MOTOR VEHICLE TAXPAYERS AS AN INTERVENING VARIABLE AT THE EAST SURABAYA SAMSAT MOBILE - Faga Audia Utama; Anna Marina; Adhar Putra Setiawan (PT. Antis International Publisher, 2024)
Taxes are one of the largest sources of government revenue funds to finance both routine and development expenditures. One of the factors that can be emphasised by the state apparatus in increasing tax compliance and awareness is by increasing knowledge and providing or setting tax sanctions. This research method uses a quantitative approach. The number of samples in this study used 929 respondents, determining the sample in this study using the Krejcie table with an error rate of 5%. The measuring instrument used is Partial Least Square (PLS) with smart PLS 4.0 software. The results of this study indicate that (1) Tax knowledge has a positive and insignificant effect on taxpayer compliance (2) Tax sanctions have a significant positive effect on taxpayer compliance (3) Taxpayer awareness has a significant positive effect on taxpayer compliance (4) Tax knowledge has a significant positive effect on taxpayer awareness (5) Tax sanctions have a significant positive effect on taxpayer awareness (6) Tax knowledge has an indirect significant positive effect on taxpayer compliance on taxpayer awareness as an intervening variable (7) Tax sanctions have an indirect significant positive effect on taxpayer compliance on taxpayer awareness as an intervening variable.